2018
DOI: 10.1016/j.jth.2018.03.007
|View full text |Cite
|
Sign up to set email alerts
|

The effect of an italian nationwide mandatory visibility aids law for cyclists

Abstract: The role of conspicuity in preventing bicycle-motorized vehicle collisions has been the subject of investigation. To date, no study has evaluated the impact on bicycle safety of legislation imposing bicycling visibility aids. The aim of the present study is to investigate whether a legislation imposing high-visibility clothing for cyclist affects bicycle safety. Data on the monthly number of vehicles (including bicycles) involved in road crashes during the period 2001-2015 were obtained from the Italian Nation… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(3 citation statements)
references
References 27 publications
0
3
0
Order By: Relevance
“…The introduction of legislation designed to reduce crashes is not always effective (e.g. Prati, 2018). However, traffic law enforcement is one method used to change driver behaviour (Bates, Soole & Watson, 2012;Stanojevic, Javanovic & Lajunen, 2013) as programs that increase compliance with traffic laws may reduce crashes and injuries (Factor, 2014;Prenzler, Manning & Bates, 2015).It is possible that there may also be other benefits given that there is emerging evidence suggesting that drivers who offend may be engaging in routine deviant and criminogenic behaviour (Nunn, 2018).…”
Section: Road Policing and Young Driversmentioning
confidence: 99%
“…The introduction of legislation designed to reduce crashes is not always effective (e.g. Prati, 2018). However, traffic law enforcement is one method used to change driver behaviour (Bates, Soole & Watson, 2012;Stanojevic, Javanovic & Lajunen, 2013) as programs that increase compliance with traffic laws may reduce crashes and injuries (Factor, 2014;Prenzler, Manning & Bates, 2015).It is possible that there may also be other benefits given that there is emerging evidence suggesting that drivers who offend may be engaging in routine deviant and criminogenic behaviour (Nunn, 2018).…”
Section: Road Policing and Young Driversmentioning
confidence: 99%
“…The efficacy of high-visibility clothing (Miller et al 2017) and protective equipment and the extent to which the latter should be the subject of legislation or indeed exhortation has been much debated. While a legislative approach in Italy mandating visibility aids for cyclists had no effect (Prati 2018), a randomised controlled trial in Denmark showed that a yellow cycle jacket reduced the collision and personal injury rates (Lahrmann et al 2017).…”
Section: Policy Implicationsmentioning
confidence: 99%
“…Visibility aids can increase the distance at which car drivers detect cyclists at night [12,13]. Currently, front reflectors, static lights, and flashing lights are widely used to improve cyclist visibility at night [14][15][16]. Further, some countries and regions have started placing legal requirements on shared bikes to improve cycling visibility at night.…”
Section: Introductionmentioning
confidence: 99%